2019
DOI: 10.1007/s12209-019-00187-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Investigation of High-Efficiency Antibacterial Liquid Dishwashing Detergent

Abstract: A high-efficiency liquid dishwashing detergent was prepared by using oregano essential oil as an antibacterial agent. The surface cleaning and antibacterial property of the detergent resolved its unifunctionality problem. The antibacterial activities of the detergent were demonstrated through a disk diffusion assay and wipe experiments with Escherichia coli and Staphylococcus aureus. Results showed that the prepared detergent was highly effective against E. coli and S. aureus. The results of chemical accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Among the toothpastes used in this study, only sodium fluoride-potassium nitrate toothpaste contained potassium nitrate and cocamidopropyl betaine in its formulations. Potassium nitrate has been reported to have strong antimicrobial activities against E. coli [34] and cocamidopropyl betaine has antibacterial activity [35].…”
Section: Discussionmentioning
confidence: 99%
“…Among the toothpastes used in this study, only sodium fluoride-potassium nitrate toothpaste contained potassium nitrate and cocamidopropyl betaine in its formulations. Potassium nitrate has been reported to have strong antimicrobial activities against E. coli [34] and cocamidopropyl betaine has antibacterial activity [35].…”
Section: Discussionmentioning
confidence: 99%
“…Liquid dishwashing is a form of detergent that is typically used as household cleaner (Dai et al, 2019). Several studies have shown the effectiveness of detergents against several whitefly populations ranging from 66.75 to 100% (Liu and Stansly, 2000;Arias et al, 2006;Boopathi et al, 2014;Khan, 2018).…”
Section: Bio-efficacy Of the Treatments Against The Adultmentioning
confidence: 99%